2021
DOI: 10.1136/jitc-2021-002644
|View full text |Cite|
|
Sign up to set email alerts
|

CD137 and PD-L1 targeting with immunovirotherapy induces a potent and durable antitumor immune response in glioblastoma models

Abstract: BackgroundGlioblastoma (GBM) is a devastating primary brain tumor with a highly immunosuppressive tumor microenvironment, and treatment with oncolytic viruses (OVs) has emerged as a promising strategy for these tumors. Our group constructed a new OV named Delta-24-ACT, which was based on the Delta-24-RGD platform armed with 4-1BB ligand (4-1BBL). In this study, we evaluated the antitumor effect of Delta-24-ACT alone or in combination with an immune checkpoint inhibitor (ICI) in preclinical models of glioma.Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 65 publications
0
24
1
Order By: Relevance
“…It has been shown for OVs that oncolysis often induces lymphocyte infiltration into the tumor [ 21 , 22 ]. As OV mediated therapeutic effects can be fostered by the treatment with ICIs [ 21 , 23 , 24 , 25 ], we were interested in whether an additional blockade of the PD-1/PD-L1 interaction further enhanced the number of TILs. For this, in one group of mice, we intratumorally injected XVir-N-31 and systemically applied nivolumab, whilst another group received a single intratumoral injection of XVir-N-31-anti-PD-L1.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown for OVs that oncolysis often induces lymphocyte infiltration into the tumor [ 21 , 22 ]. As OV mediated therapeutic effects can be fostered by the treatment with ICIs [ 21 , 23 , 24 , 25 ], we were interested in whether an additional blockade of the PD-1/PD-L1 interaction further enhanced the number of TILs. For this, in one group of mice, we intratumorally injected XVir-N-31 and systemically applied nivolumab, whilst another group received a single intratumoral injection of XVir-N-31-anti-PD-L1.…”
Section: Resultsmentioning
confidence: 99%
“…The presence of the blood-brain barrier(BBB) is thought to be a barrier to drug action in intracranial tumors, attenuating their efficacy ( 39 ). It should also be mentioned that gliomas have long been considered “cold” tumors with a high degree of immunosuppression ( 40 ). As a result, more research into the immune microenvironment of glioblastoma is required to offer a foundation for immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Results showed that Delta-24-ACT exerted a cytotoxic effect on human glioma cell lines and tumors in the murine models, implying that the expressed 4-1BBL was able to stimulate T cells in vitro and in vivo. The combination of Delta-24-ACT with an anti-PD-L1 antibody extended the median survival and generated immune memory, which indicated the potential of combining immune-virotherapy with immune checkpoint inhibitors as a promising and effective strategy for the treatment of poorly infiltrated tumors such as glioma [ 119 ].…”
Section: Oncolytic Virusesmentioning
confidence: 99%